Answer:
2x^3 - 2x^2 - 12x
Step-by-step explanation:
2x(x - 3)(x + 2)
= 2x ( x^2 + 2x -3x - 6)
= 2x (x^2 - x - 6)
= 2x^3 - 2x^2 - 12x (answer).
Answer:
256.25
Step-by-step explanation:
if you have a 20% discount then you are paying 80% if the original cost.
so 80% of the original price is 205
.80x = 205
x = 205/.80
Answer:
x=1
Step-by-step explanation:
5x-(x+1)=5-2x
distribute
5x-x-1 = 5-2x
4x-1 = 5-2x
add 2x on each side
4x-1+2x = 5-2x+2x
6x -1 = 5
add 1 on each side
6x-1+2 = 5+1
6x = 6
divide by 6
6x/6 = 6/6
x = 1
Answer:
what are u trying to ask
Step-by-step explanation: